Prevalence of diabetes mellitus and its associated risk factor assessment among elderly in urban area of Punjab - Arora, Ishan; Singh, Shairoly; Bhuwal, Parveen Kumar; Singh, Shireen (International Journal Of Community Medicine And Public Health, 2019)
Background: Greek Physician Aretaeus (30-90CE) observed a disease with symptoms such as constant thirst (polydipsia), excessive urination (polyuria) and loss of weight. Based on these findings, he named the condition ‘diabetes’, meaning ‘a flowing through. Diabetes mellitus is a serious public health concern, not just because of its high prevalence or the chronicity, but more importantly because of its life-threatening micro vascular and macro vascular complications which are often silent and undetected until the advanced and irreversible stage has developed, and they may even appear years before the diagnosis of diabetes. Methods: A cross-sectional study was carried out on elderly (60 years and above). This study was intended to measure prevalence of diabetes mellitus and associated risk factors. Results: In present study, the prevalence of diabetes was found to be higher among female participants at 41.98% compared to males at 25.90%. Prevalence of diabetes was highest in the age group of 60-70 years. Mean BMI (28.05) of female participants was higher compared to the BMI of the male participants which was 25.52. It was observed that the prevalence of diabetes increases with increase in BMI. Conclusions: Early detection and treatment of these chronic morbidities should be done with regular health check- ups and screening of these diseases before they can cause permanent damage to health of individual or death. People should also be educated and counselled about monitoring their health parameters to ensure early detection and treatment.